KETAHANAN TIGA SPESIES ARACHIS TERHADAP BERCAK DAUN AKHIR (CERCOSPORIDIUM PERSONATUM BERK. ET CURT.) PADA PEMBERIAN DAN TANPA PEMBERIAN MANKOZEB - Setyo Dwi Utomo dan Hasriadi Mat Akin . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2004)
The resistance of three species of Arachis to late leaf spot (Cercosporidium personatum) with and without application of mankozeb. The use of resistant cultivars and application of fungicide are effective means to control late leafspot. Resistant genotypes of peanut is required as a parent for hibridization to develop high-yielding cultivars resistant to late leaf spot. The objective of this study were to evaluate the resistance of 11 genotypes from three species of Arachis to late leaf spot (C. personatum) with and without application of mankozeb. The experiment was arangged ia a split splot design with three replications. The main plots were fungicide treatment (treated and untreated). Fungicide mankozeb ( 4 g/l, 500 l/ha) was applied at 28, 40, 52, 64 and 76 days after planting. The sub-plots were genotypes of species Arachis, i.e., 7 lines of cultivated peanut (Archis hypogaea) from ICRISAT, 2 national varieties (Gajah and Kelinci), and two wild species (A. cardenasii, and A. pintoi). The two wild species were imune to late leaf spot so that they can be utilized as resistant parent in wide hybridization to develop a superior cultivars. ICGV 88262 was more resistant than Gajah and Kelinci. Because its yield tend to be lower than Gajah and Kelinci, ICGV 88262 also can be utilized as resistant parent in hibridization. Mankozeb was efective and substantially reduced yield losses of cv. Gajah. Mankozeb should be aplied in cultivation of cv. Gajah to control late leafspot.